Awake Transcortical Approach Resection of Dominant Posterior Cingulate Gyrus Glioma: 2-Dimensional Operative Video. Issue 1 (28th July 2019) - Hameed, N U Farrukh; Wu, Bin; Gong, Fangyuan; Zhang, Jie; Chen, Hong; Wu, Jinsong
Abstract: Two techniques, the translongitudinal cerebral fissure and transfrontal cortical approach, can be employed to resect posterior cingulate gyrus tumors. We demonstrate the transcortical technique comprising of multimodal imaging guidance and awake brain mapping which enabled maximum safe resection of dominant cingulate gyrus glioma. The patient, a 49-yr-old female, came to clinic after experiencing headache for a month. Initial magnetic resonance imaging (MRI) scans revealed a nonenhancing lesion of the left posterior cingulate gyrus. Three-dimensional magnetic resonance spectroscopy was used to analyze the choline/N-acetyl-aspartate index (CNI) which strongly suggested a low-grade glioma diagnosis. In surgery, after creating a tailed bone window and dural opening, strip electrode was placed across the central sulcus for continuous motor evoked potential monitoring. Next, direct cortical stimulation was done to map functional cortical areas. The transcortical approach was chosen at this point because many veins hindered hemisphere retraction. Noneloquent cortical incisions were made and the tumor was carefully debunked with a cavitron ultrasonic surgical aspirator. The corpus callosum marked the deep end of dissection. Subcortical mapping combined with diffusion tensor imaging tractography-based navigation was performed to localize motor and language tracks. Intraoperative MRI evaluation confirmed a gross total resection. Pathological and molecular analysis revealed a World Health Organization Grade II IDH-wildtype Diffuse Astrocytoma diagnosis. Since the patient falls in high-risk group, she was also administered radiation and chemotherapy. Long-term cognitive evaluation follow-up of the patient showed she had good functional recovery with no obvious long-term deficits. Informed patient consent was obtained.